# Solve for q -(69q-12)=-6(13q+4)

-(69q-12)=-6(13q+4)
Simplify -(69q-12).
Apply the distributive property.
-(69q)–12=-6(13q+4)
Multiply.
Multiply 69 by -1.
-69q–12=-6(13q+4)
Multiply -1 by -12.
-69q+12=-6(13q+4)
-69q+12=-6(13q+4)
-69q+12=-6(13q+4)
Simplify -6(13q+4).
Apply the distributive property.
-69q+12=-6(13q)-6⋅4
Multiply.
Multiply 13 by -6.
-69q+12=-78q-6⋅4
Multiply -6 by 4.
-69q+12=-78q-24
-69q+12=-78q-24
-69q+12=-78q-24
Move all terms containing q to the left side of the equation.
Add 78q to both sides of the equation.
-69q+12+78q=-24
9q+12=-24
9q+12=-24
Move all terms not containing q to the right side of the equation.
Subtract 12 from both sides of the equation.
9q=-24-12
Subtract 12 from -24.
9q=-36
9q=-36
Divide each term by 9 and simplify.
Divide each term in 9q=-36 by 9.
9q9=-369
Cancel the common factor of 9.
Cancel the common factor.
9q9=-369
Divide q by 1.
q=-369
q=-369
Divide -36 by 9.
q=-4
q=-4
Solve for q -(69q-12)=-6(13q+4)

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top